2019
DOI: 10.3389/fmicb.2019.00388
|View full text |Cite
|
Sign up to set email alerts
|

NanoFe3O4 as Solid Electron Shuttles to Accelerate Acetotrophic Methanogenesis by Methanosarcina barkeri

Abstract: Magnetite nanoparticles (nanoFe3O4) have been reported to facilitate direct interspecies electron transfer (DIET) between syntrophic bacteria and methanogens thereby improving syntrophic methanogenesis. However, whether or how nanoFe3O4 affects acetotrophic methanogenesis remain unknown. Herein, we demonstrate the unique role of nanoFe3O4 in accelerating methane production from direct acetotrophic methanogenesis in Methanosarcina-enriched cultures, which was further confirmed by pure cultures of Methanosarcina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…For instance, S. oneidensis MR-1 increased methane production only by 5% after 6 days of incubation with CH 3 F, whereas the increase reached 22.5% without CH 3 F. Calculations shows that acetoclastic methanogenesis accounted for 70-80% of produced methane, and, conversely, CO 2 reduction accounted for only 20-30% of produced methane (Table 1). Our findings are supported by pure culture and metatranscriptomic data showing that Fe 3 O 4 nanoparticles act as electron shuttles to stimulate acetoclastic methanogenesis [20,21]. However, for this study and the two studies mentioned above [20,21], the experiments were performed with acetate as the sole carbon source.…”
Section: Increase Of Methane Production Performance With S Oneidensisupporting
confidence: 75%
See 2 more Smart Citations
“…For instance, S. oneidensis MR-1 increased methane production only by 5% after 6 days of incubation with CH 3 F, whereas the increase reached 22.5% without CH 3 F. Calculations shows that acetoclastic methanogenesis accounted for 70-80% of produced methane, and, conversely, CO 2 reduction accounted for only 20-30% of produced methane (Table 1). Our findings are supported by pure culture and metatranscriptomic data showing that Fe 3 O 4 nanoparticles act as electron shuttles to stimulate acetoclastic methanogenesis [20,21]. However, for this study and the two studies mentioned above [20,21], the experiments were performed with acetate as the sole carbon source.…”
Section: Increase Of Methane Production Performance With S Oneidensisupporting
confidence: 75%
“…are not always detected in improved methane production systems [19]. Two recent studies suggested that conductive magnetite accelerates acetoclastic methanogenesis [20,21]. First, Fu et al showed that nanoFe 3 O 4 acts as solid electron shuttles to accelerate acetoclastic methanogenesis by Methanosarcina barkeri in pure cultures [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small difference in redox potentials of these components, it has been proposed that an electrically quantized membrane is important to solidify electron flow efficiency and prevent from thermodynamic dissipation (Duszenko and Buan, ). Accordingly, it has been suggested that the penetration of magnetite nanoparticles into Methanosarcina membrane and entering the cell cytoplasm enhanced the membrane electric quantization and hence the methanogenesis in Methanosarcina (Fu et al ., ). It is unlikely, however, that the penetration of exogenous nanoparticles will not cause a disturbance on cell interior integrity (John et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The interaction between NM and microorganisms is significant, and it is at the basis of an emerging discipline dubbed nanomicrobiology. It is notable that microorganisms naturally synthesize NP as a mechanism to detoxify their environment from toxic elements, normally heavy metals, [167] or use them as electrodes to assist direct interspecies electron transfer [168] or as reservoirs to release with molecular precision some essential elements (upon NM dissolution) at the site of action, for instance bactericidal ions (Ag + ) [169] or pro-proliferating ones (Fe 2+ ). [170] The NM size and water solubility allow them to finely integrate into the biological machinery.…”
Section: Nanomaterials and Interaction With Bacteriamentioning
confidence: 99%